2023
DOI: 10.1212/wnl.0000000000207284
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of Prednisolone to Treat Bell Palsy in Children

Abstract: Background and Objectives:Bell’s palsy is the third most frequent diagnosis in children with sudden onset neurological dysfunction. The cost-effectiveness of treating Bell’s palsy with prednisolone in children is unknown. We aimed to assess the cost-effectiveness of prednisolone in treating Bell’s Palsy in children compared with placebo.Methods:This economic evaluation was a prospectively planned secondary analysis of a double-blinded, randomized, placebo-controlled superiority trial (BellPIC) conducted from 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…The CHU9D is a generic MAUI designed for children and adolescents aged 7–17 [ 20 ]. Xiong et al [ 21 ] reported that the CHU9D can be used for children between the ages of 5 and 18, with parent-report for children aged 5–7 years and self-report for children aged 8–18 years. It consists of nine questions that assess child’s worry, sadness, pain, fatigue, annoyance, schoolwork, sleep, daily routine, and ability to participate in activities.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The CHU9D is a generic MAUI designed for children and adolescents aged 7–17 [ 20 ]. Xiong et al [ 21 ] reported that the CHU9D can be used for children between the ages of 5 and 18, with parent-report for children aged 5–7 years and self-report for children aged 8–18 years. It consists of nine questions that assess child’s worry, sadness, pain, fatigue, annoyance, schoolwork, sleep, daily routine, and ability to participate in activities.…”
Section: Methodsmentioning
confidence: 99%
“…Caregivers provide their views on their child over the preceding 24 hours using a 5-level response rating, ranging from 0 (no problems) to 5 (severe problem) [ 22 ]. The CHU9D can be completed by either children themselves or a proxy [ 21 ]. In this study, a proxy-report was used because many non-ambulatory children with CP were unable to complete questionnaires by themselves.…”
Section: Methodsmentioning
confidence: 99%
“…The article by Xiong, et al, 2 which reports the results of a CEA conducted alongside a randomized, blinded placebo-controlled clinical trial of prednisolone in children with Bell palsy (BellPIC), 3 begs this very question. The BellPIC RCT looked at the outcome of complete clinical recovery at 1, 3, and 6 months and found no difference in recovery rates at any of the end points in the placebo and intervention groups.…”
mentioning
confidence: 99%
“…As part of a larger body of work to improve the care of children with Bell’s palsy, we recently completed a randomised controlled trial (RCT) of prednisolone for the treatment of Bell’s palsy. The study did not find any benefit of prednisolone in the recovery of complete facial function at 1 month,4 17 as measured using the clinician-administered House-Brackmann Scale (primary outcome). Given the lack of available data on pain in children with Bell’s palsy, the aim of the current study was to describe the prevalence and severity of pain experienced by children with Bell’s palsy over the 6-month period following symptom onset.…”
Section: Introductionmentioning
confidence: 81%